Infants preferentially learn from surprising teachers. (26th May 2022) - Stahl, Aimee E.; Woods, Larissa
Abstract: Infants have sophisticated knowledge about the physical world, and show enhanced learning about objects that violate physical principles. However, it is unknown whether infants also preferentially learn from the individual who produces an outcome that violates expectations. We investigated whether 15‐month‐old infants ( N = 48) selectively imitate individuals who produce surprising outcomes. In Experiment 1, infants watched an experimenter hide a ball and produce an expected outcome in which the ball was revealed where it was hidden, or a surprising outcome in which the ball was revealed in a different location. The experimenter then demonstrated a novel action: using her head to activate a light while her hands were free. Infants imitated that novel action more if the experimenter had previously produced a surprising than an expected outcome. In Experiment 2, infants witnessed the experimenter produce the surprising outcome, then use her head to activate the light while her hands were occupied. Infants did not differentially imitate the head‐touch action relative to either condition in Experiment 1, perhaps indicating a tension between surprise‐induced learning and rational imitation. These experiments show that surprising events are pedagogical opportunities: infants selectively learn from surprising individuals, but also may account for rationality in their surprise‐induced social learning.